187k views
2 votes
Solve. 7x−6=8+5x Enter your answer in the box. x =

User Naman Gala
by
5.4k points

2 Answers

2 votes

Answer

7(7x)-6=8+5(7x)

49-6=8+35

43=43

43

User Mwillbanks
by
6.4k points
4 votes

Answer:

x = 7

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define equation

7x - 6 = 8 + 5x

Step 2: Solve for x

  1. Subtract 5x on both sides: 2x - 6 = 8
  2. Add 6 to both sides: 2x = 14
  3. Divide 2 on both sides: x = 7

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: 7(7) - 6 = 8 + 5(7)
  2. Multiply: 49 - 6 = 8 + 35
  3. Subtract/Add: 43 = 43

Here we see that 43 does indeed equal 43.

∴ x = 7 is a solution of the equation.

User Nat Naydenova
by
5.9k points